1982
DOI: 10.1017/s0021859600030161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spray cooling and wallowing on potassium concentration of erythrocytes in buffaloes (Bos bubalis) during summer

Abstract: SUMMARYForty-five normal lactating buffaloes from Punjab Agricultural University, Dairy Farm herd, were used for this study and were divided into three groups as group I (control), group II (showers) and group III (wallowing). The study was conducted from May to September in two periods, May–June as period I (hot and dry) and July–September as period II (hot and humid). Potassium concentration was estimated on a flame photometer. The overall average values (m-equiv/l) were found to be lowest in the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Sprinkling was reported to be helpful in maintaining normal sodium and potassium levels [ 18 ]. However, it was suggested that wallowing was more effective than spraying in maintaining electrolyte balance during summer stress in buffalo [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sprinkling was reported to be helpful in maintaining normal sodium and potassium levels [ 18 ]. However, it was suggested that wallowing was more effective than spraying in maintaining electrolyte balance during summer stress in buffalo [ 46 ].…”
Section: Discussionmentioning
confidence: 99%